The education of a Canadian : my life as a scholar and activist - Skilling, H. Gordon (Harold Gordon), 1912-2001 (Published for Carleton University by McGill-Queen's University Press, 2000)
Gordon Skilling writes candidly of each way station in this personal odyssey: the idealism of his student years at the University of Toronto and Oxford; his presence in Czechoslovakia on the eve of the Nazi, and later Soviet, invasions; his opposition to the Marshall Plan, NATO, and U.S. intervention in Korea; the effect of McCarthyism on his academic life; his involvement with the Czech and Slovak dissident movements and finally the Velvet Revolution. The Education of a Canadian also captures conversations with writers, journalists, scholars, and myriad friends throughout Russia and Eastern Europe (including Havel, Djilas, and Sakharov), making this history a distinctly human yet forceful document of profound humanity and international scope.